The Effect of Islamic Service Quality on Patient Loyalty in Private Islamic Hospitals - Sofyan Arfi; Indah Fatmawati (Journal of Business and Management Review, 2026)
Research Aims: This study aims to examine the effects of Islamic Service Quality (ISQ) on Islamic Hospital Reputation (IHR), Patient Satisfaction (PS), Patient Trust (PT), and Patient Loyalty (PL) in private Islamic hospitals. It also investigates the mediating roles of IHR, PS, and PT in the relationship between ISQ and PL. Design/methodology/approach: A quantitative approach with an explanatory research design was employed. Primary data were collected from 200 patients of private Islamic hospitals using purposive sampling. Data were gathered through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Research Findings: The results indicate that ISQ has significant positive effects on IHR, PS, and PT. IHR significantly influences PS, while PS significantly affects PT. Furthermore, IHR, PS, and PT significantly enhance PL. The findings also demonstrate that IHR, PS, and PT mediate the relationship between ISQ and PL. Theoretical Contribution/Originality: This study contributes to the Islamic healthcare service literature by developing an integrated framework that links Islamic service quality, Islamic hospital reputation, patient satisfaction, patient trust, and patient loyalty. The findings highlight that patient loyalty is influenced not only by Islamic service quality directly but also through the mediating roles of hospital reputation, patient satisfaction, and patient trust, providing a more comprehensive understanding of loyalty formation in Islamic healthcare settings. Keywords: Islamic Service Quality, Islamic Hospital Reputation, Patient Satisfaction, Patient Trust, Patient Loyalty.